Power factor correction for energy efficient at public hospital of Manokwari - Panggei, Yahja; Pasalli, Yulianus Rombe; Paisey, Fourys Yudo Setiawan; Rehiara, Adelhard (Institute for Advanced Science Social, and Sustainable Future, 2023)
The power factor grades are an indicator to determine the effectiveness of the electric power either distributed or used by consumers. A high power factor indicates that the electrical loads are using energy efficiently. Due to the increase in inductive load, there will be a decrease in the power factor, which in turn affects the distribution of electrical energy. In this research, an investigation has been carried out to observe the background that influences the low power factor at public hospital (RSUD) of Manokwari and recommend the need for a basis for improving the power factor at the hospital. Primary data on lighting and electrical equipment, along with their respective electric power capacities and power factors, are collected and measured onsite. Then the data is analysed based on the theoretical basis of power factor improvement. Based on the investigation, there are two focus points in the hospital to be observed, i.e., motor pumps and total load at the main panel. The calculation results show that pump motors 2 and 3 need to be compensated by increasing the power factor to 0.9 so that reactive power is reduced to 1.42 kVAR and 1.24 kVAR, respectively. In the same way, apparent power can also be upgraded to 0.85 kVA and 1.46 kVA by installing bank capacitors of 30.35 mF and 26.63 mF, respectively. On the other hand, the largest load connected to the main panel needs to be corrected to reduce the reactive power and apparent power to 17.86 kVAR and 9.5 kVA through the installation of a capacitor bank of 387.75 mF. This correction will increase energy efficiency while gaining economic benefits on both electricity bills and waiving penalties.